Ring-like spatial distribution of laser accelerated protons in the ultra-high-contrast TNSA-regime. (3rd April 2018) - Becker, G A; Tietze, S; Keppler, S; Reislöhner, J; Bin, J H; Bock, L; Brack, F-E; Hein, J; Hellwing, M; Hilz, P; Hornung, M; Kessler, A; et al.
Abstract: The spatial distribution of protons accelerated from submicron-thick plastic foil targets using multi-terawatt, frequency-doubled laser pulses with ultra-high temporal contrast has been investigated experimentally. A very stable, ring-like beam profile of the accelerated protons, oriented around the target's normal direction has been observed. The ring's opening angle has been found to decrease with increasing foil thicknesses. Two-dimensional particle-in-cell simulations reproduce our results indicating that the ring is formed during the expansion of the proton density distribution into the vacuum as described by the mechanism of target-normal sheath acceleration. Here—in addition to the longitudinal electric fields responsible for the forward acceleration of the protons—a lateral charge separation leads to transverse field components accelerating the protons in the lateral direction.